Student and Graduate Mobility in Armenia - Cairns, David; Sargsyan, Marine (Springer International Publishing : Imprint: Palgrave Pivot, 2019)
Based on exploratory research with students and graduates conducted in Armenia and its diaspora during summer 2018, Cairns and Sargsyan provide insight into some of the challenges involved in moving abroad, focusing on three different destinations: Russia, the United States and the European Union. Additionally, Student and Graduate Mobility in Armenia considers issues that have an impact on life chances for highly qualified young people who wish to remain in Armenia, including perceptions of corruption in the local labour market and hopes for the future following the Velvet Revolution of spring 2018. This research will be of interest to students and scholars of mobility, youth, employment and education. .